Implementasi BOCARI Sebagai Solusi Penerangan Daerah Wisata di Kampung Wisata Dangean - Andi Widiyanto; Alan Kusuma; Wawan Sadtyo Nugroho (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
This community service program aims to implement BOCARI (Botol Cahaya Matahari) as an alternative lighting solution in tourist areas without electricity networks, specifically in Kampung Wisata Dangean, Boyolali. The lack of electricity infrastructure has limited the operational hours of Pasar Ngatpaingan, one of the village’s main attractions. The program applied a participatory approach through the installation of BOCARI, development of digital information boards, and training on digital marketing for the local community. Results show that the application of BOCARI extended market operational hours into the evening, increased visitor numbers, and reduced production costs. Furthermore, digital promotion activities improved online visibility of local tourism and strengthened the integration of history, education, and creative economy attractions. This initiative not only supports SDG 7 (Affordable and Clean Energy) but also contributes to SDG 8 (Decent Work and Economic Growth) and SDG 11 (Sustainable Cities and Communities)..